SELECTION FOR CATATONIA: EFFECT ON THE SEXUAL FUNCTION AND ESTROUS CYCLE SYNCHRONIZATION - D. V. Klochkov; T. A. Alekhina (Вавиловский журнал генетики и селекции, 2014)
Body, ovary, and uterus weights; estrous cycle; dopamine and norepinephrine levels in the hypothalamus; and testosterone levels in blood plasma have been recorded in 2–3-month old GC female rats selected for elevated catatonia response and compared with the outbred Wistar stock. The body weights of GC rats are lower, and the cyclic linkage between the ovaries and the uterus is disrupted, as apparent from a reduced diestrus ovary weight and a lower estrogen-dependent uterus weight increase in comparison to Wistar. A statistically significant synchronization of estrous cycles is observed in GC rats kept in standard cages, five to seven animals per cage. It includes a larger number of matches of individual estrus phases to form a group estrus phase of their 4–5-day long estrous cycle. Synchronized estrus phases include 50–60 % of GC rats, which is significantly more than in Wistar rats (30–40 %). With reduced dopamine and norepinephrine levels in hypothalami of GC rats, the levels of these monoamines are higher in the estrus and low in the diestrus. Testosterone levels in diestrus GC females are higher than in estrous or Wistar ones.